Experimental Study of Coherent Collaborative Processing Method in Distributed Automotive Radar - A. A. Kuzin; S. E. Kuznetsov; A. V. Miakinkov; R. S. Fadeev; S. A. Shabalin (Известия высших учебных заведений России: Радиоэлектроника, 2025)
Introduction. Intelligent driver assistance systems are increasingly employing radar systems to detect, resolve, and track various classes of targets. The use of MIMO-based distributed systems allow the characteristics of object resolution by angle to be significantly improved. However, this is associated with the difficulty to ensure a coherent mode of processing data entering from two or more radar systems. This work compares a millimeter wavelength range radar system with improved angular resolution with a monostatic system. The issue of ensuring synchronization of radars comprising the system under study is addressed.Aim. To increase the angular resolution of a distributed radar system with tandem coherent signal processing of two MIMO radars.Materials and methods. The resolution of a system consisting of two spaced radars was investigated experimentally using a fully functional layout. Algorithms for phase synchronization and collaborative digital signal processing, along with appropriate software, were developed.Results. The use of a common external reference signal source in MIMO radars makes it possible to implement a coherent system operation mode. Placement of two spaced MIMO radars ensures the formation of a bistatic virtual antenna array, which doubles the angle resolution, compared with a radar whose number of receiving channels is two times smaller than the size of a bistatic virtual array.Conclusion. The conducted experimental studies demonstrated an increase in angular coordinate resolution during the formation of a bistatic virtual antenna array. The use of an external reference generator ensures the coherent operation of two radars, improving the accuracy of mutual phase synchronization in the channels of bistatic subarrays by several degrees.